Lifestyle, Brand Image, Product Attributes and How They Affect on Purchasing Decisions - Ego Dermawan; R. Agus Baktiono; Muchamad Arif (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2021)
This study aims to determine the effect of lifestyle, brand image, and product attributes on purchasing decisions on Samsung Smartphone products in East Surabaya. The sample was 97 respondents. The instrument was questionnaire. It used the IBM SPSS 25 software to analyzed data. TBased on the results of the regression analysis, the equation was Y=3,314+0.389X1+0.026X2+0.137X3+e. Then, the result of the test showed that the data is valid and reliable. It was also no multicollinearity, heteroscedasticity, and normally distributed. The T-test showed that the Lifestyle (X1) had a t-count value of 2.875 and significant 0.005. whereas product attributes (X3) which had a t-count value of 2.677 with significance 0.009, which meant that the X1 and X2 variables affected purchasing decisions, while the Brand Image (X2) variable had no effect on Purchase Decisions because it had t value of 0.368 with a significance of 0.713. The results of F test, showed that the X1, X2, and X3 variables had a simultaneous effect on purchasing decisions with the F count result of 35,439 with significance of 0.000. Then, the results of the determination test was 51.8%.